Pengaruh Neurodynamic Mobilization Terhadap Perubahan Kemampuan Aktivitas Fungsional Pada Pasein Cervical Root Syndrome Di Rumah Sakit Universitas Brawijaya Malang - Dewi Wulaningsih; Yohanes Deo Fau; Angria Pradita; Achmad Fariz (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
This study aims to observe changes in functional activity ability in cervical root syndrome (CRS) patients after neurodynamic mobilization. Pre-test and post-test quasi-experimental research design using neck disability index (NDI) measurements before and after 6 treatments for 3 weeks. Using a non-probability sampling technique, it was conducted on 20 samples of men and women in the 40-45 year age group.This study obtained a median value of 63.00 on NDI measurements before neurodynamic mobilization and a median value of 22.00 on NDI measurements after neurodynamic mobilization showed a significant value of the Wilcoxon test of 0.00.Neurodynamic mobilization technique is effective in improving functional activity ability in CRS patients.